INDICES ANTHROPOMETRIC, SKIN FOLDS AND RELATED TO CHRONIC METABOLIC DISORDERS IN STUDENTS OF 11 TO 16 YEARS OF THE NETWORK STATE AREA NORTH OF TERESINA-PI (Fiep Bulletin - online, 2015)
The increase in the percentage of fat in adolescents is a fact that has been spreading alarmingly rising statistics of a disease that falls under an international designation of a global epidemic of the XXI century: obesity, which is associated with a number of co- morbidities. Obesity in childhood and adolescence has become a global problem and it is known that a sedentary lifestyle, coupled with inappropriate eating habits are the main reasons for its early manifestation. To identify possible weight problems should be done with the individual a child, since the prevention and / or treatment can reduce the spread of this disease. Thus, an important role of the Physical Educator is to act preventively through the physical evaluation of anthropometric indices in schools. The objective of this research was to trace the anthropometric profile of students from 6th to 8th grade of elementary school (5th correspondent will 7th grade), aged between 11 and 16 years, of both sexes, students at a state school in the area North Teresina-Pi, in Porenquanto neighborhood. The study was conducted with 300 adolescents of this institution for 30 days between the months of September and October, during the morning shift, in which a physical evaluation was performed for measurement of body mass index - BMI and skinfolds - DC. In addition, an interview was also completed, with the consent of parents and the school board, in order to investigate the possible incidence of chronic diseases within the family and examine the frequency of weekly physical activity among students. The results showed that there is a significantly high rate of overweight / obesity by analyzing both BMI and DC, which showed a ratio of 61.1% for chronic diseases and family 43.3% for inactive adolescents.
Keywords: Obesity; Prevention; Anthropometric Indices.